1998
DOI: 10.1007/bf02783970
|View full text |Cite
|
Sign up to set email alerts
|

Determination of reference ranges for elements in human scalp hair

Abstract: Expected values, reference ranges, or reference limits are necessary to enable clinicians to apply analytical chemical data in the delivery of health care. Determination of references ranges is not straightforward in terms of either selecting a reference population or performing statistical analysis. In light of logistical, scientific, and economic obstacles, it is understandable that clinical laboratories often combine approaches in developing health associated reference values. A laboratory may choose to: 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Since the elements are present in the hair at higher levels, more sensitive and accurate analysis results can be expected [44]. As such, it has been suggested that hair mineral analysis can be a cost-effective means of screening an individual's nutritional status [45]. As before we had discussed that low serum Zn may be the result of an acute phase response rather than primary zinc deficiencies, we suggested that the analysis of human hair instead of serum can be a useful way to understand the permanent record of Zn status in patients with MI.…”
Section: Discussionmentioning
confidence: 98%
“…Since the elements are present in the hair at higher levels, more sensitive and accurate analysis results can be expected [44]. As such, it has been suggested that hair mineral analysis can be a cost-effective means of screening an individual's nutritional status [45]. As before we had discussed that low serum Zn may be the result of an acute phase response rather than primary zinc deficiencies, we suggested that the analysis of human hair instead of serum can be a useful way to understand the permanent record of Zn status in patients with MI.…”
Section: Discussionmentioning
confidence: 98%
“…This gap is gradually being filled. For example, Druyan et al [27] obtained reference values for Americans, Park et al [28] for Koreans, and Senofonte et al [29] did the same for an Italian population. However, these values can differ because of the different analytical methods used.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Environmental Protection Agency (EPA), human hair is one of the most important biological materials for worldwide environmental monitoring and the International Atomic Energy Agency uses hair to monitor global trends of element levels [36]. Hair as a biological tissue is unique in respect that it serves as an accumulator for trace elements, and in addition, it is formed in relatively short period of time and remains isolated from the metabolic events in the human body and its metal content can reflect the body status for a long period [34,37,38].…”
Section: Introductionmentioning
confidence: 99%